Phytochemical, Antibacterial And Cytotoxic Evaluation Of Raphiostylis Beninensis [Hook F. Ex Planch] Stem Bark Extracts - LASISI, A. A.,; FOLARIN, O. M.,; DARE, E. O,; AKINLOYE O. A.,; FISUYI, M. O., (International Journal of Pharma and Bio Sciences, 2011)
Methanol and ethyl acetate (stem-bark) extracts of Raphiostylis beninensis were investigated for their phytochemical, antibacterial and cytotoxic properties. Phytochemical analysis of ethyl acetate extracts of R. beninensis revealed alkaloids (1.10 ± 0.20 mg/kg), flavonoids (6.10 ± 0.10 mg/kg), saponins (5.30 ±0.15 mg/kg) and tannins (2.10 ± 0.20 mg/kg). Methanol of extract R. beninensis contained alkaloids (1.50 ±0.10 mg/kg), flavonoids (6.24 ± 0.20 mg/kg), saponins (7.50 ±0.10 mg/kg) and tannins (1.32 ± 0.03 mg/kg). The stem bark methanol and ethyl acetate extracts of Raphiostylis beninensis inhibited all tested strains Escherichia coli, Bacillus subtilis, Salmonella typhii and Staphyllococcus aureus at 20 mg/ml and 50 mg/ml respectively. The brine shrimp lethality test on the methanol and ethyl acetate extracts of Raphiostylis beninensis revealed cytotoxic activities with LC50 of 3.20 and 2.50 µg/ml.